Does a family history of adenomatous colon polyp(s) in a first‐degree relative pose an increased risk of developing colon cancer?. Issue 4 (April 2018) - Clements, Ernestine; Gamble, Lena; Way, Nathan; Smith, Lacy; Waits, John B.
Abstract : EVIDENCE‐BASED ANSWER : Yes. A positive family history of adenomatous polyps doubles a person's risk for developing colorectal cancer (SOR: B, meta‐analysis of case‐control trials and a casecontrol study). Similarly, patients with adenomas are 40% more likely to have a family history of colon cancer than patients without polyps (SOR: B, cohort trial).